2010
DOI: 10.1111/j.1365-2958.2010.07051.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatic marks are associated with the repression of secondary metabolism clusters in Aspergillus nidulans

Abstract: Fungal secondary metabolites are important bioactive compounds but the conditions leading to expression of most of the putative secondary metabolism (SM) genes predicted by fungal genomics are unknown. Here we describe a novel mechanism involved in SM-gene regulation based on the finding that, in Aspergillus nidulans, mutants lacking components involved in heterochromatin formation show de-repression of genes involved in biosynthesis of sterigmatocystin (ST), penicillin and terrequinone A. During the active gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
295
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(310 citation statements)
references
References 56 publications
(81 reference statements)
11
295
2
2
Order By: Relevance
“…Histone-3 trimethylation at lysine 9 had been found to be associated with the repression of secondary metabolism clusters in A. nidulans. LaeA is presumably involved in reversal of this heterochromatin signature inside the cluster (Reyes-Dominguez et al, 2010). The interaction of SasA with histone-2B is consistent with the finding that histone-2B can stimulate histone methyltransferase activity when modified at lysine 34 by ubiquitin (Wu et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Histone-3 trimethylation at lysine 9 had been found to be associated with the repression of secondary metabolism clusters in A. nidulans. LaeA is presumably involved in reversal of this heterochromatin signature inside the cluster (Reyes-Dominguez et al, 2010). The interaction of SasA with histone-2B is consistent with the finding that histone-2B can stimulate histone methyltransferase activity when modified at lysine 34 by ubiquitin (Wu et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
“…An additional role of LaeA is its requirement for Hülle cell formation (Sarikaya Bayram et al, 2010). LaeA carries a conserved SAM-binding site typical for nuclear protein methyltransferases (Bok and Keller, 2004;Kozbial and Mushegian, 2005) and there is accumulating evidence for an epigenetic control function of LaeA by chromatin remodeling (Reyes-Dominguez et al, 2010). A misregulation of the SAM synthetase encoding gene in A. nidulans might therefore affect development and secondary metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ReyesDominguez et al (28) showed that acetylation of these H3 residues in the promoter region of the sterigmatocystin biosynthesis regulatory gene aflR was increased when the fungus was shifted to sterigmatocystin production conditions. However, a high level of acetylation did not necessarily lead to a high expression of cluster genes.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that under noninducing conditions the acetylation status of histones in this region is kept relatively low by constitutive, reciprocal activities of HATs and HDACs and that FB-inducing conditions cause a shift in this equilibrium. That histone acetylation is involved in the regulation of the aflatoxin cluster in A. parasiticus and of the sterigmatocystin cluster in A. nidulans was also demonstrated by ChIP assays (22,25). The HDAC-encoding gene HDF1 of Fusarium graminearum was also very recently shown to influence deoxynivalenol production, along with virulence, sexual and asexual reproduction, and development (12).…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have begun to identify molecular players in chromatin remodeling in fungi, which seems to impact SM synthesis more extensively than primary cell functions. Epigenetic control of fungal SM has been confirmed for sterigmatocystin, penicillin, and terrequinone A (22,28). Those studies highlighted the importance, in fungal SM, of reversible posttrans-lational modifications of histones (the proteins around which DNA is wrapped to form nucleosomes) and of the enzymes that carry out such modifications (30).…”
mentioning
confidence: 95%